Aircraft evacuation procedure using discrete event simulation - Noraini Azwani, Arifin (2019)
This thesis is about aircraft evacuation procedure using Discrete Event Simulation (DES) method. The evacuation process must be carried out in the event of an emergency such as engine failure, fire, and smoke. The aircraft must be emptied within 90 seconds to reduce the risk of loss of life. This is because, it is possible for passengers to be saved after 90 seconds to safely thin. Usually, the process of transfer process is done manually. However, manual tests require a high cost and take a long time. The aircraft management had to find more than 300 people to serve as passengers during training. Long time is needed to explain to everyone about the procedures and actions to take. The crews also need to engage during the evacuation. This involves many parties. Therefore, aircraft evacuation test using these simulations are created. The purpose of this study is to study whether the flight test is better than manual simulation.